Racing Stripes - Du Chau, Frederik; Muniz, Frankie, 1985-; Moore, Mandy, 1984-; Duncan, Michael Clarke; Foxworthy, Jeff.; Jackson, Joshua, 1978-; Eggby, David; Isham, Mark.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2005)
A traveling circus accidentally leaves behind a baby zebra. The baby is then rescued by horse farmer Nolan Walsh, who takes him home to his young daughter Channing. "Stripes" is soon introduced to the farm's misfit troupe of barnyard residents. The Walsh farm borders the Turfway Racetrack, where highly skilled thoroughbreds compete for the ultra-prestigious Kentucky Crown. From the first moment Stripes lays eyes on the track, he's hooked. He knows that if he could just get a chance, he could leave all those other horses in the dust. What he doesn't know is - he's not exactly a horse. But with characteristic zeal, he devotes himself to training for the big time.
DVD, region , full screen (1.33:1) presentation; Dolby Digital 5.1 surround.
English, dubbed French or dubbed Spanish dialogue, French or Spanish subtitles; closed-captioned.
Title from container.
Voices: Frankie Muniz, Mandy Moore, Michael Clarke Duncan, Jeff Foxworthy, Joshua Jackson, Snoop Dogg, Joe Pantoliano, Michael Rosenbaum, Steve Harvey, David Spade, Fred Dalton Thompson, Dustin Hoffman, Whoopi Goldberg.
Bruce Greenwood, Hayden Panettiere, Caspar Poyck, Gary Bullock, Wendie Malick, M. Emmet Walsh.
Director of photography, David Eggby ; senior animator, Patrick Tasse ; art director, Jonathan Hely-Hutchinson ; editor, Tom Finan ; music, Mark Isham ; costume designer, Jo Katsaras ; production designer, Wolf Kroeger ; visual effects supervisor, Eric Mises-Rosenfield ; visual effects animation supervisor, Alexander Williams.
Keywords: Zebras -- Drama; Farms -- Kentucky -- Drama; Racetracks (Horse racing) -- Kentucky -- Drama; Cebras -- Teatro; Granjas -- Kentucky -- Teatro; Video recordings for the hearing impaired; Feature films; Youth -- Animation -- Feature; Comedy -- Feature; Video recordings for the hearing impaired